2012
DOI: 10.1111/j.1478-5153.2012.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the reliability, effectiveness and applications of Licox in traumatic brain injury

Abstract: Licox offers new insights into cerebral pathology and physiology. The continuous bedside monitoring provides real-time data that can be used to improve patient management and prognosis in specialist units by trained and experienced staff. More research is required to understand the limitations of this technology and why it is not in widespread use. RELEVENCE TO CLINICAL PRACTICE: A clinical tool that could be utilized more often in the right setting to improve care to patients suffering from TBI by disseminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…For sensors calibrated in vitro then implanted, the matrix of the calibration solution should reflect that of the in vivo matrix. Keddie and Rohman noted that differences between the calibration solution and in vivo test environment most assuredly cause the probe to function “differently” . The main differences between in vivo and in vitro calibrations are: the mass transport through a standard solution is different due to diffusion and convection, there are numerous interferences from a complex sample matrix in vivo, causing the limited operational stability of sensors in biological media .…”
Section: Resultsmentioning
confidence: 95%
“…For sensors calibrated in vitro then implanted, the matrix of the calibration solution should reflect that of the in vivo matrix. Keddie and Rohman noted that differences between the calibration solution and in vivo test environment most assuredly cause the probe to function “differently” . The main differences between in vivo and in vitro calibrations are: the mass transport through a standard solution is different due to diffusion and convection, there are numerous interferences from a complex sample matrix in vivo, causing the limited operational stability of sensors in biological media .…”
Section: Resultsmentioning
confidence: 95%
“…Oxygen tension monitoring is used for several purposes in clinical practice, especially in neurosurgery and neuroanesthesia for the monitoring of brain oxygenation during the treatment of traumatic injuries, cerebral aneurisms, and other neurological conditions (Cerejo, Silva, Dias, & Vaz, ; Cyrous, O'Neal, & Freeman, ; Gelabert‐Gonzalez, Fernandez‐Villa, & Ginesta‐Galan, ; Keddie & Rohman, ). It has also been used for experimental purposes to determine the correlation between renal blood flow and tissue oxygenation at different intra‐abdominal pressures (Wiesenthal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade several studies showed a correlation between low brain oxygen levels and higher mortality rate and unfavorable outcome [ 182 , 183 ]. Combined monitoring of ICP and brain tissue oxygen tension has shown to be superior to ICP alone [ 184 , 185 ]. Additionally, brain oxygenation offers a new variable to evaluate cerebral autoregulation and cerebrovascular reactivity as mentioned before in Table 3 .…”
Section: Neuromonitoring After Tbimentioning
confidence: 99%